Winter hunting behavior and habitat selection of wolves in a low‐density prey system. Issue 1 (14th December 2017) - Johnson, Ian; Brinkman, Todd; Lake, Bryce; Brown, Casey
Abstract : The functional response is the relationship between food intake rates and prey density, and is shaped by factors including handling time, predator speed, habitat or prey movement. For many predator—prey systems, the density‐dependent functional response is represented by a type II or type III functional response. Determination of the relationship type is important, as managers can often predict the response of predators to changing prey densities. In wolf—moose ( Canis lupus—Alces alces ) systems with relatively high prey density, the functional response often follows a predicted type II functional response. However, in a very low prey‐density system, wolves have previously been shown to escape the density dependent phase of the functional response and demonstrated kill rates mimicking high prey‐density systems. We conducted a study to evaluate winter wolf movements between moose kills in the Yukon Flats, Alaska where moose exist at densities <0.2 km −2 . Our research objectives were to understand whether habitat selection when moving and specific behaviors could be mechanisms used by wolves to maintain kill rates that mimic those in high prey density systems and if those behaviors may allow wolves in our study system to escape a density dependent functional response. We used GPS collars to characterize wolf travel paths between kills to estimate wolf travel speed, movement distance, time between kills, and handling time of each kill. Our results demonstrated selection for frozen river corridors by wolves and provided new information on long‐distance movements in a low prey‐density system. These adaptations may influence the functional response by moderating the effect of low prey densities.